Potential Combination of Cermai (Phyllanthus acidus) and Mulberry (Morus alba) Fruit Extract as a Candidate For Tyrosinase Inhibitor - Susanti, Erna; AS, Nour Athiroh; Ramadhan, Majida; Mardhiyah, Mardhiyah; Noor, Mahanem Mat (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Melanin, a pigment derived from UV radiation, is crucial in preventing skin damage and can cause aesthetic and dermatological problems such as hyperpigmentation or hypopigmentation. Melanogenesis is a complex process involving enzymes and cytokines, with UV being a primary contributor. Tyrosinase is a key enzyme in melanin synthesis. This study aims to test the potential of combining cermai fruit extract (CE) and mulberry fruit (ME) as a tyrosinase inhibitor. The tests included antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, total phenolic content using the Folin Ciocalteu method, flavonoid content using the AlCl3 colorimetric method, and sun protection factor (SPF) value using UV-Vis spectrophotometric method. The results showed that the highest total phenolic content was observed in (CE), followed by the combination of ME: CE in the ratio of 1:3, 1:1, 3:1, and then ME. The same pattern was seen in the flavonoid content assay results. The antioxidant activity, as indicated by the IC50 values, followed the following order CE 418.30%; ME: CE (1:3) 400.49%; ME: CE (1:1) 367.73%; ME: CE (3:1) 358.04%; and ME 344.43%. The highest SPF value was observed in ME. It can be concluded that this study shows that the combination of CE and ME extracts has potential as a tyrosinase inhibitor and skin protective agent from hyperpigmentation due to UV exposure.